A Historical Perspective On The Economics Of The Ownership Of Mineral Rights Ownership - F. T. Cawood (The Southern African Institute of Mining and Metallurgy, 1998)
?It is in the interest of stability and investor confidence that the healthy and necessary debate on such a (minerals) policy should soon find its way to consensus.? (President Nelson Mandela at the104th (1995), AGM of the South African Chamber of Mines) Inauguration of the new political dispensation in South Africa initiated a dynamic period in the historical development of its minerals policy. The process of substituting the current South African mineral policy framework with an acceptable ?post apartheid? system, started soon after the 1994 election of the African National Congress (ANC) government. The Green Paper on a Minerals and Mining Policy for South Africa released for public discussion in February 1998, calls for radical transformation in mineral rights ownership. A shift towards exclusive state ownership of mineral rights, away from the present dual system of private and state ownership, is the most significant proposal. The current holders of mineral rights, or their nominees, who lawfully enjoyed security of tenure under past and present mineral laws are opposed to this transformation because mineral rights were often acquired at considerable cost. The situation is compounded by poor public record-keeping and passive mineral rights administration over a very long period. This paper represents a summary of the historical developments leading to the current legislative environment and forms the basis for any discussion on which future sculpturing of South Africa?s policy regarding mineral rights can take place. One cannot plan for the future without considering the past!